2015
DOI: 10.1007/s13277-015-3452-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-140-3p suppressed cell growth and invasion by downregulating the expression of ATP8A1 in non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) as a class of small noncoding RNA molecules regulate the expression of targeted gene. The dysregulation of microRNAs is reported to be involved in carcinogenesis and tumor progression. Here, we identified miR-140-3p as a downregulated microRNA in most cancer tissues including lung cancer tissues, compared with their normal counterparts. MiR-140-3p was observed to perform its tumor suppressor function via its inhibition on cell growth, migration and invasion but its induction of cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Collectively, the key findings in this study support the notion that miR-140-3p plays an important role in HCC progression, providing evidence for the mechanism that miR-140-3p-targeted GRN inhibition mediates the MAPK signaling pathway, by The first main finding of our study was that miR-140-3p was under-expressed in HCC and GRN upregulated in HCC. Importantly, miR-140-3p has been identified as a downregulated miRNA in most cancers, such as non-small cell lung cancer, 27 and basal-like early-stage breast cancer. 28 Apart from that, miR-140 is the most stable miRNA in HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the key findings in this study support the notion that miR-140-3p plays an important role in HCC progression, providing evidence for the mechanism that miR-140-3p-targeted GRN inhibition mediates the MAPK signaling pathway, by The first main finding of our study was that miR-140-3p was under-expressed in HCC and GRN upregulated in HCC. Importantly, miR-140-3p has been identified as a downregulated miRNA in most cancers, such as non-small cell lung cancer, 27 and basal-like early-stage breast cancer. 28 Apart from that, miR-140 is the most stable miRNA in HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al () showed that miRNA‐92a promotes growth in NSCLC cells via targeting PTEN. In addition, miR‐140‐3p suppressed cell growth and invasion by downregulating the expression of ATP8A1 in NSCLC (Dong et al, ). For another, several miRNAs serve as oncogenes in NSCLC (Ye et al, ; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a human tumor suppressor that accounts for the majority of cellular serine/threonine phosphatase activity [40]. ATP8A1 is a member of P4-ATPase family with a role in the formation of membrane ruffles to promote cell migration [41]. BLPAP (Bladder cancer-associated protein) is a highly conserved protein among species displaying tissue-specific expression patterns, but also tissue-specific functions being both a tumor suppressor and a tumor promoting [42].…”
Section: Resultsmentioning
confidence: 99%